Real-time deformability cytometry: On-the-fly cell mechanical phenotyping - Otto, Oliver; Rosendahl, Philipp; Mietke, Alexander; Golfier, Stefan; Herold, Christoph; Klaue, Daniel; Girardo, Salvatore; Pagliara, Stefano; Ekpenyong, Andrew; Jacobi, Angela; Wobus, Manja; Toepfner, Nicole; et al. (Nature methods, 2015)
We introduce real-time deformability cytometry (RT-DC) for continuous cell mechanical characterization of large populations (>100,000 cells) with analysis rates greater than 100 cells/s. RT-DC is sensitive to cytoskeletal alterations and can distinguish cell-cycle phases, track stem cell differentiation into distinct lineages and identify cell populations in whole blood by their mechanical fingerprints. This technique adds a new marker-free dimension to flow cytometry with diverse applications in biology, biotechnology and medicine.
CRIS-Team Scopus Importer:2022-08-05